PENYISIHAN TSS DAN KEKERUHAN AIR PERMUKAAN DENGAN PROSES KOAGULASI SISTEM HIDROLIS - Firra Rosariawari; Dwi Agus Novianto (EnviroUS, 2022)
The condition of raw water is getting worse due to increased pollution of water resources, namely surface water. The raw water treatment methods that can be applied are very diverse, one of which is physical and chemical treatment, namely the flocculation coagulation process followed by a sedimentation process using Poly Aluminum Chloride (PAC). The purpose of this study was to determine the effect of variations in the type and concentration of coagulants on the coagulation process of the hydraulic system on the turbidity of water in river water and to determine the effect of settling time on the coagulation process of the hydraulic system on the turbidity of Bono Pabean, Sedati-Sidoarjo. The results obtained in this study using a parshall flume with a neck size of 2.54 cm obtained an optimal discharge of 12 L/minute with a sampling time of 120 minutes. The discharge has a velocity gradient (G) of 2427/sec, Froude number (NFr) 3.84 and Reynolds number (NRe) 8683. Meanwhile, the optimal coagulant dose in this treatment is 130 mg/L and the effectiveness obtained by hydraulic stirring with using parshall flume and baffle channel, managed to eliminate 2.25% of the Turbidity parameter.